THE FIRST CASE REPORT OF MAJOR RIGHT-SIDED HEPATECTOMY IN INFANT PATIENT IN NATIONAL CHILDREN’S MEDICAL CENTER - Konstantin Semash; Timur Dzhanbekov; Murod Abduazizov; Ahror Alimov (Central Asian Journal of Medicine, 2023)
Introduction. Liver resection is a surgical method of treatment of benign and malignant tumors including in infant patients. Materials and methods. We want to demonstrate a case of major right-sided hepatectomy in infant patient due to rare giant anastomosing hemangioma tumor firstly performed in our center. Results. Right hepatectomy in 5-month-old child was performed. Operative time was 175 minutes. Estimated blood loss was 50 milliliters. In the early postoperative period, the patient developed moderate post-resection liver failure, which was treated conservatively. No surgical complications occurred. Patient was discharged on 7-th postoperative day with normal liver function. Conclusion. The results of the case demonstrated the feasibility and safety of the major liver resection procedure for infant patients in our center.